Cross-cultural implications of evidence based dentistry - Francesco Chiappelli (Brazilian Journal of Oral Sciences, 2015)
Evidence based dentistry is a process of systematic evaluation of the research evidence for directed implications and applications in the day-to-day reality of clinical practice. In order to be successful, the integration of research evidence into the practice of clinical dentistry relies on the ability of dentists to identify appropriately designed and conducted research, whose data are correctly analyzed. The current practice of dentistry must increasingly rest on the judicious utilization of the best available evidence. However, questions arise as to the validity of the published research to individual clinical needs in different sociocultural environments, as to whether or not published research can indeed be trusted, and as to what might be the most readily protocols for the evaluation of published research evidence. These issues are discussed herein in the context of the practical example of the chewing sticks, often used in tropical countries as a preventive measure for oral health and hygiene.